Associations between number of steps and health outcomes in children and adolescents: a systematic review and meta-analysis - Stefan Stojanović; Olena Andrieieva; Nebojša Trajković (BMC Public Health)
Abstract Background Today’s public health discourse prioritizes the health and well-being of children and adolescents. As step counts include both light and moderate-to-vigorous physical activities, and monitoring steps has become a popular method for assessing daily physical activity, it is critical to gain a better understanding of how measuring daily steps may contribute to overall health in children and adolescents. The aim of this study was to thoroughly review the studies that investigated the associations between daily number of steps (DNoS) and health outcomes (HO) in children and adolescents. Methods Electronic searches were conducted in PubMed, Google Scholar, Cochrane, MEDLINE, Web of Science, SPORTDiscus (2000 –January 2024.). Key terms such as number of steps, daily steps, average steps, physical activity, health outcomes were used. The primary outcomes were (1) body composition/obesity risk factors; (2) cardiorespiratory fitness (CRF); and (3) cardiovascular risk factors. Secondary outcomes were psychological/psychosocial parameters (sleep habits, i.e. quality of life). We assessed the methodological quality of each trial using AXIS quality assessment tool. In instances where continuous data emanated from two or more trials, a meta-analysis was undertaken. Results The main findings of this systematic review and meta-analysis are that an increased number of DNoS is associated with better HO in children and adolescents, as evidenced by improvements in body mass index (BMI), body weight, waist circumference, body fat percentage, and cardiorespiratory fitness (i.e., VO2max). However, due to a dearth of studies and conflicting results from current studies, no inferences can be drawn about the correlations between DNoS and sleep quality, quality of life, or cardiovascular risk factors (i.e., blood pressure). Across most of the studies, the average correlation between the DNoS and HO reflected a small, but significant, association with a small effect size. Conclusions Our findings highlight the importance of daily physical activity, as evidenced by the association between the number of steps and health outcomes in children and adolescents. Trial registration PROSPERO # CRD42024523729.